Foam

By using branched block copolymers to prepare foam for sports shoes midsole components, the problem of difficulty in achieving multiple properties at the same time is solved, and lightweight, wear-resistant, good elasticity and hydrolysis resistance is achieved. The effect is also in line with the needs of low-carbon trends.

CN119505337APending Publication Date: 2025-02-25IND TECH RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411173324.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-08-22
Filing Date
2024-08-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing sports shoe midsole material is difficult to achieve lightweight, wear-resistant, good elasticity, hydrolysis resistance and non-deformability at the same time. The foam of the commercially available thermoplastic polyester elastomer is insufficient due to insufficient melt strength and crystallization performance. The bubble size is small and the density is high, making it difficult to meet the low-carbon trend demand.

Method used

Using foamed bodies composed of block copolymers, the block copolymers contain aromatic polyester blocks and aliphatic polymer blocks, which are connected by polyol dehydrogenation residues to form a branched structure and improve melt strength. and crystalline.

Benefits of technology

The foamed body is achieved with low density, high flexibility, high rebound rate and high physical properties maintenance. It is suitable for high-end sports products and shoe materials, and can be prepared using recycled materials to meet low carbon requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention provides a foam. The foaming body is composed of a foaming material and a plurality of foam holes, the plurality of foam holes are arranged in the foaming material, and the foaming material is prepared from a foaming composition. The foaming composition comprises 0.01 to 2.0 parts by weight of a flow promoter and 100 parts by weight of a block copolymer. The block copolymer comprises a first block, a second block and a linking group; the first block is linked to the second block through the linking group. The first block is an aromatic polyester block; the second block is an aliphatic polyether block, an aliphatic polyester block or an aliphatic polycarbonate block; and the linking group is a residue obtained by removing hydrogen from a polyhydric alcohol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a foamed body. Background Art

[0002] Traditional sports shoes are extremely complex in structure, usually made of uppers and soles made of multiple shoe parts made of different materials and assembled with glue. Different parts can provide the required performance for sports shoes, for example, the midsole part of the sole should have properties such as light weight, wear resistance, good elasticity, hydrolysis resistance and non-deformation.

[0003] Currently, most midsole components are made of ethylene / vinyl acetate copolymer (EVA). In order to achieve the required performance of midsole components, ethylene / vinyl acetate copolymer must be produced through high-temperature chemical cross-linking and molded chemical foaming processes, but this also causes the problem of being unable to be recycled. Although polyurethane elastomer (TPU) has gradually been used in some high-end sports shoes due to its advantages such as wear resistance and good physical properties, TPU has poor hydrolysis and yellowing resistance, and insufficient compression resistance, which limits its application feasibility.

[0004] The industry has begun to seek new recyclable alternative materials, among which thermoplastic polyester elastomer (TPEE) has gradually attracted attention due to its good physical properties.

[0005] The currently commercially available thermoplastic polyester elastomers cannot meet the future low-carbon trend. Because the foam prepared using the commercially available linear thermoplastic polyester elastomer has insufficient melt strength and crystallization performance, it can only obtain a smaller bubble size and a higher bubble density, which makes it difficult to lighten and has a poor rebound rate. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a foam body in order to at least partially solve the above technical problems. Therefore, the specific technical solutions provided by the present invention are as follows.

[0007] According to an embodiment of the present invention, the present invention provides a foam body, which is composed of a foaming material and a plurality of foam cells, and the plurality of foam cells are arranged in the foaming material, wherein the foaming material is prepared by a composition, and the composition comprises: 0.01 to 2.0 parts by weight of a flow aid, and 100 parts by weight of a block copolymer. According to an embodiment of the present invention, the block copolymer comprises a first block, a second block, and a connecting group; the first block is connected to the second block through the connecting group; the first block is an aromatic polyester block; the second block is an aliphatic polyether block, an aliphatic polyester block, or an aliphatic polycarbonate block; and the connecting group is a residue of a dehydrogenated polyol, wherein the polyol is a triol, a tetraol, a pentaol, a hexaol, a heptaol, or an octaol.

[0008] According to an embodiment of the present invention, the present invention provides a method for preparing a foam, which is used to prepare the foam of the present invention. The method for preparing the foam may include providing a composition, and performing a foaming process using the composition to obtain the foam. DETAILED DESCRIPTION

[0009] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0010] The foam of the present invention and its preparation method are described in detail below. It should be understood that the following description provides many different embodiments or examples for implementing different forms of the present invention. The specific elements and arrangements described below are only briefly described in the present invention. Of course, these are only used as examples and are not limitations of the present invention. The "about" used in the present invention refers to the value including the value and the acceptable deviation range when the technicians in the field consider the measurement problem and the measurement error (that is, the limitation of the measurement system). For example, "about" can be expressed in one or more standard deviations of the value or in the value of ±20%, 10%, 5% of the value. The number given here is an approximate number, that is, in the absence of a specific description of "about", "approximately", "substantially", the meaning of "about", "approximately", "substantially" can still be implied. In the present invention, the expression of "a to b" means including a value greater than or equal to a and a value less than or equal to b.

[0011] It is understood that, although the terms "first", "second", "third", etc. may be used herein to describe various elements, components, regions, layers, and / or parts, these elements, components, regions, layers, and / or parts should not be limited by these terms, and these terms are only used to distinguish different elements, components, regions, layers, and / or parts. Therefore, a first element, component, region, layer, and / or part discussed below may be referred to as a second element, component, region, layer, and / or part without departing from the teachings of some embodiments of the present invention.

[0012] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood by those skilled in the art. It will be further understood that terms defined in commonly used dictionaries should be interpreted as having the same meaning as that in the relevant art and the content of the present invention, and unless explicitly defined herein, will not be interpreted in an idealized or overly formal sense.

[0013] The embodiment of the present invention provides a foam and a preparation method thereof, for example, a foam containing a specific thermoplastic polyester elastomer (TPEE) and a preparation method thereof. Commercially available thermoplastic polyester elastomers have a linear structure and a fast crystallization rate, so the melt strength in the molten state is insufficient, and the solidification rate is also fast when the temperature is lowered, which is not conducive to foaming processing and forming. It is usually easy to produce broken holes, or larger-sized bubbles, or defects such as uneven distribution of bubble size. According to an embodiment of the present invention, the foam provided by the present invention can be composed of a foaming material and a plurality of bubbles, wherein the foaming material is prepared from a composition, and the composition includes a flow aid, and a specific block copolymer (such as a thermoplastic polyester elastomer block copolymer). The block copolymer includes a first block, a second block, and a connecting group. Since the connecting group is a residue of dehydrogenated polyol, the block copolymer has a branched structure, the molecular chain entanglement degree of the block copolymer is increased, the melt strength of the block copolymer is further optimized, and the crystallinity and fluidity are improved. In this way, the foam of the present invention can have low density, high flexibility, high resilience, and high physical property maintenance rate (such as tensile strength maintenance rate, flexural strength maintenance rate, tear strength maintenance rate, and compression permanent deformation maintenance rate), and is suitable for application in the fields of high-end sports goods or shoe materials.

[0014] In addition, according to an embodiment of the present invention, recycled polyester (such as polyethylene terephthalate) can be used as a raw material, and through a glycol depolymerization agent, a reaction catalyst and a chemical depolymerization process, an aromatic polyester oligomer (as a hard segment of the block copolymer of the present invention) is obtained, and further reacted with an aliphatic polymer (such as an aliphatic polyether, an aliphatic polyester, or an aliphatic polycarbonate) (as a soft segment of the block copolymer of the present invention) and a polyol to obtain the block copolymer of the present invention. Based on the above, the foam of the present invention can be made using recycled materials, which meets the requirements of reducing carbon emissions.

[0015] According to an embodiment of the present invention, the present invention provides a foam, wherein the foam may be composed of a foam material and a plurality of pores, and the plurality of pores are arranged in the foam material. The foam material may be prepared from a composition. According to an embodiment of the present invention, the composition may include 0.01 to 2.0 parts by weight (e.g., 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.2, 0.5, 0.7, 1.0, 1.2, 1.5, 1.7, or 1.9 parts by weight) of a flow aid, and 100 parts by weight of a block copolymer. The block copolymer may be a block copolymer having a branched structure, such as a thermoplastic polyester elastomer block copolymer. The block copolymer may include a first block, a second block, and a linking group, wherein the first block is connected to the second block through the linking group. The first block may be an aromatic polyester block. The second block may be an aliphatic polymer block, such as an aliphatic polyether block, an aliphatic polyester block, or an aliphatic polycarbonate block. In addition, the linking group may be a dehydrogenated residue of a polyol.

[0016] According to an embodiment of the present invention, the polyol may be a trihydric alcohol, a tetrahydric alcohol, a pentahydric alcohol, a hexahydric alcohol, a heptahydric alcohol, or an octahydric alcohol.

[0017] According to an embodiment of the present invention, the block copolymer may include at least one first block, at least one second block, and at least one linking group. According to an embodiment of the present invention, the block copolymer may include at least one first block, at least one second block, and at least one linking group.

[0018] According to an embodiment of the present invention, in the block copolymer, the ratio of the total weight of the first block to the total weight of the second block may be about 1:4 to 4:1, for example, 1:3, 1:2, 1:1, 2:1, or 3:1. When the block copolymer has too high a first block content, it exhibits too high a hardness, and too low an elongation and resilience, and the melt strength is insufficient, and a foam with excellent pore structure cannot be obtained. When the block copolymer has too high a second block content, it exhibits insufficient tensile strength, and too low a crystallization rate and crystallinity, and cannot be smoothly cooled and solidified during the foaming process. The resulting foam has poor pore morphology and poor compression permanent deformation rate, as well as physical property maintenance rate.

[0019] According to an embodiment of the present invention, in the block copolymer, the content of the linking group is 0.1wt% to 2wt% (e.g., 0.2wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, or 1.8wt%), based on the total weight of the first block and the second block. When the content of the linking group of the block copolymer is within the above range, the block copolymer may have a branched structure and an appropriate degree of molecular chain entanglement, so that the foam of the present invention has low density, high flexibility, high resilience, high melt strength and uniform cell structure.

[0020] According to an embodiment of the present invention, the density of the foam of the present invention may be about 0.05 g / mL to 0.2 g / mL (e.g., 0.06 g / mL, 0.07 g / mL, 0.08 g / mL, 0.09 g / mL, 0.1 g / mL, 0.13 g / mL, 0.15 g / mL, or 0.19 g / mL). According to an embodiment of the present invention, the rebound rate (i.e., the rebound rate of the falling ball) of the foam may be about 60% to 80% (e.g., 61%, 62%, 65%, 70%, or 75%). The density and rebound rate of the foam of the present invention may be measured according to the method specified in the standard ASTM D3574.

[0021] According to an embodiment of the present invention, the hardness (i.e., Shore A hardness) of the block copolymer may be about 30D to 70D (e.g., 40D, 50D, or 60D). The Shore A hardness of the block copolymer may be measured according to the method specified in ASTM D2240.

[0022] According to an embodiment of the present invention, at a temperature of the melting point (melting temperature, Tm) of the block copolymer + 30°C, the melt strength of the block copolymer may be about 10mN to 20mN (e.g., 11mN, 12mN, 13mN, 14mN, 15mN, 16mN, 17mN, 18mN, or 19mN). The melt strength of the block copolymer can be measured using a rheometer (AR-G2, manufactured by TA Instruments, USA) with a melt strength tester (Rheotens), the test temperature is the melting point of the block copolymer + 30°C, and the roller traction acceleration is 24mm / s. The melting point (Tm) of the block copolymer can be measured using a differential scanning calorimetry (DSC) (model Discovery DAS 25, manufactured by TAInstruments, Inc.). If the melt strength of the block copolymer is too high, the fluidity will be greatly reduced, and the foaming gas will not be able to mix smoothly with the melt, resulting in processing failure or uneven foaming. If the melt strength of the block copolymer is too low, it will cause the phenomenon of broken bubbles and combined bubbles to form large bubbles during the cell growth stage, ultimately leading to the deterioration of the properties of the foam.

[0023] According to an embodiment of the present invention, at a temperature of the melting point of the block copolymer + 30°C and a shear rate of 100 sec -1 Under the condition of s (e.g. 10Pa s to 1500Pa s). Melt viscosity can be measured using a capillary rheometer (ASTM D3835) at a shear rate of 100 sec. -1 The test temperature is the melting point of the block copolymer + 30°C, the plate length is 25 mm, and the gap is 200 µm.

[0024] According to an embodiment of the present invention, the intrinsic viscosity (IV) of the block copolymer of the present invention may be about 1.0 dL / g to 1.8 dL / g (e.g., 1.1 dL / g, 1.2 dL / g, 1.3 dL / g, 1.4 dL / g, 1.5 dL / g, 1.6 dL / g, or 1.7 dL / g). The intrinsic viscosity of the block copolymer is measured according to the method specified in ASTM D4603-2003.

[0025] According to an embodiment of the present invention, the cell particle size distribution D90 of the foam may be about 10 μm to 400 μm (e.g., 10 μm, 30 μm, 50 μm, 70 μm, 100 μm, 150 μm, 200 μm, 250 μm, 300 μm, or 350 μm). The particle size distribution D90 means that 90% of the total volume of the powder has a diameter less than the value defined by the D90. According to an embodiment of the present invention, the particle size distribution D90 is measured according to the method specified in ISO 13322-1:2004.

[0026] According to an embodiment of the present invention, the first block can be obtained by an esterification reaction between an aromatic dicarboxylic acid and an aliphatic diol. According to an embodiment of the present invention, the aromatic dicarboxylic acid can be terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, or a combination thereof. According to an embodiment of the present invention, the aliphatic diol may be ethylene glycol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,4-cyclohexanedimethanol, or a combination thereof.

[0027] According to an embodiment of the present invention, the first block may be a polyethylene terephthalate block, a poly(trimethylene terephthalate) block, a poly(butylene terephthalate) block, a polyethylene isophthalate block, a poly(trimethylene isophthalate) block, or a poly(butylene isophthalate) block.

[0028] According to an embodiment of the present invention, the weight average molecular weight of the first block may be in the range of 800 g / mol to 3000 g / mol (e.g., 1000 g / mol, 1100 g / mol, 1500 g / mol, 2000 g / mol, 2100 g / mol, 2500 g / mol, or 2700 g / mol). If the weight average molecular weight of the first block is too high, the reactivity of the terminal reactive functional group may be too low, or the steric hindrance of the long molecular chain may be too large, which may ultimately result in the inability to increase the subsequent molecular weight. If the weight average molecular weight of the first block is too low, the microphase separation of the hard segment and the soft segment may not be smoothly formed, which may ultimately affect the mechanical properties and resilience of the material.

[0029] According to an embodiment of the present invention, the second block may be a polyoxyethylene glycol block, a polypropylene glycol block, a polytetramethylene ether glycol block, a polyethylene propylene glycol block, a polyethanediol-co-adipate glycol block, a polybutanediol-co-adipate glycol block, a polyhexanediol-co-adipate glycol block, a polycaprolactone glycol block, or a poly(hexamethylene carbonate) glycol block.

[0030] According to an embodiment of the present invention, the weight average molecular weight of the second block may be in the range of 500 g / mol to 2000 g / mol (e.g., 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, 1500 g / mol, 1700 g / mol, or 2000 g / mol). If the weight average molecular weight of the second block is too high, it will form a phase separation morphology with the first block, resulting in the inability to smoothly increase the molecular weight. If the weight average molecular weight of the second block is too low, the microphase separation of the hard segment and the soft segment cannot be smoothly formed, which ultimately affects the mechanical properties and resilience of the material.

[0031] According to an embodiment of the present invention, the polyol is an aliphatic polyether triol, an aromatic polyether triol, an aliphatic polyester triol, an aromatic polyester triol, an aliphatic polyether tetraol, an aromatic polyether tetraol, an aliphatic polyester tetraol, an aromatic polyester tetraol, an aliphatic polyether pentaol, an aromatic polyether pentaol, or a aromatic polyether pentaol having a weight average molecular weight of 800 g / mol to 3000 g / mol (e.g., 1000 g / mol, 1100 g / mol, 1500 g / mol, 2000 g / mol, 2100 g / mol, 2500 g / mol, or 2700 g / mol). aliphatic polyester pentaol, aliphatic polyester pentaol, aromatic polyester pentaol, aliphatic polyether hexaol, aromatic polyether hexaol, aliphatic polyester hexaol, aromatic polyester hexaol, aliphatic polyether heptaol, aromatic polyether heptaol, aliphatic polyester heptaol, aromatic polyester heptaol, aliphatic polyether octaol, aromatic polyether octaol, aliphatic polyester octaol or aromatic polyester octaol.

[0032] According to an embodiment of the present invention, the weight average molecular weight of the block copolymer may be about 20000 g / mol to 100000 g / mol (e.g., 30000 g / mol, 40000 g / mol, 50000 g / mol, 60000 g / mol, 70000 g / mol, 80000 g / mol, or 90000 g / mol). If the weight average molecular weight of the block copolymer is too high, the block copolymer has poor fluidity after hot melting, resulting in poor tensile strength and tear strength, and rebound rate of the obtained foam. If the weight average molecular weight of the block copolymer is too low, the block copolymer melt strength is poor, resulting in poor cell morphology (including broken bubbles, different cell sizes) of the obtained foam, and further affecting mechanical strength and rebound rate. The weight average molecular weight (Mw) of the block copolymer of the present invention can be measured by gel permeation chromatography (GPC) (using polystyrene as a standard to make a calibration curve).

[0033] According to an embodiment of the present invention, the flow aid may be stearic acid, stearate, stearamide, paraffin, oleamide, tristearin (HTG), monostearin (GMB), or a combination thereof.

[0034] According to an embodiment of the present invention, the composition for forming the foaming material of the present invention may further include 0.01 to 1 parts by weight of an antioxidant. The antioxidant may be a hindered phenol antioxidant, an ester antioxidant, a thioester antioxidant, a phosphite antioxidant, or a combination thereof. For example, the antioxidant may be 2,6-di-tert-butyl-4-methylphenol, 2,5-di-tent-amylhydroquinone, 2,5-di-tert-butylhydroquinone, 4,4'-butylidene-bis(3-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-methyl 2,2′-methylene-bis(4-methyl-6-tert-butylphenol), 2,2′-methylene-bis(4-ethyl-6-tert-butylphenol), 4,4′-thiobis(2-t-butyl-5-methylphenol), 2,2′-thiodiethylbis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] diethyl bis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate]), pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate]), 4,4'-thiobis(2-methyl-6-t-butylphenol), 2,2'-thiobis(6-t-butyl-4-methylphenol), octadecyl-[3-(3,5-di-t-butyl-4-hydroxyphenyl)-propionate]5-di-t-butyl-4-hydroxyphenyl)-propionate]), triethyleneglycol-bis-[3-(3-t-butyl-4-hydroxy-5-methylphenol)propionate]), thiodiethylene bis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]), 6,6′-di-t-butyl-2,2′-thiodi-p-cresol, dioctadecyl 3,3′-thiodipropionate, trisnonylphenol phosphite, triphenyl phosphite phosphite), diphenyl phosphite, phenyl diisodecyl phosphite, diphenyl isodecylphosphite, diphenyl isooctyl phosphite, tetraphenyl dipropyleneglycol diphosphite, or a combination thereof.

[0035] According to an embodiment of the present invention, the composition for forming the foaming material of the present invention may further include other additives as needed, such as a heat stabilizer, a light stabilizer, a softener, a plasticizer, an anti-adhesive agent, an antistatic agent, a melt strength enhancer, an impact modifier, or a combination thereof. The amount of the additive added is not particularly limited, and those skilled in the art may adjust it according to actual needs. According to an embodiment of the present invention, the amount of each of the additives added may be about 0.01 parts by weight to 5 parts by weight.

[0036] According to an embodiment of the present invention, the composition for forming a foaming material of the present invention may be composed of 100 parts by weight of the block copolymer of the present invention and 0.01-2.0 parts by weight of a flow aid. According to other embodiments of the present invention, the composition for forming a foaming material of the present invention may be composed of 100 parts by weight of the block copolymer of the present invention, 0.01-2.0 parts by weight of a flow aid, and 0.01-1.0 parts by weight of an antioxidant.

[0037] According to an embodiment of the present invention, the composition used to form the foaming material of the present invention may be composed of a main component and a secondary component. Among them, the main component is composed of a block copolymer, a flow aid, and an antioxidant. And the secondary component is composed of an additive. According to an embodiment of the present invention, the foaming composition of the present invention may be substantially composed of a copolymer, a flow aid, and an antioxidant, and the secondary component is an additive. The content of the main component is greater than or equal to 90wt%, based on the total weight of the main component and the secondary component.

[0038] According to an embodiment of the present invention, the composition for forming a foaming material of the present invention has a branched structure and an appropriate degree of molecular chain entanglement because the block copolymer used has a branched structure and an appropriate degree of molecular chain entanglement, so it is not necessary to add a crosslinking agent or a chain extender (that is, the composition for forming a foaming material of the present invention may not contain a crosslinking agent or a chain extender) to achieve the technical purpose of improving the tensile and tear strength, flexibility, resilience, and compression permanent deformation retention rate of the foam. In addition, according to an embodiment of the present invention, the composition for forming a foaming material of the present invention does not contain a polymer prepared using styrene as a reactive monomer.

[0039] According to an embodiment of the present invention, the block copolymer of the present invention may be a reaction product of an aromatic oligomer (used to form a first block (i.e., a hard segment)), an aliphatic oligomer (used to form a second block (i.e., a soft segment)), and a polyol. In addition, the above reaction may be carried out in the presence of a catalyst, wherein the catalyst may be organic zinc (e.g., zinc acetate), organic titanium (e.g., tetrabutyl titanate), organic tin, sulfuric acid, potassium hydroxide, potassium carbonate, 4-dimethylaminopyridine, antimony oxide, or a combination thereof. The amount of the catalyst may be 0.01wt% to 1wt% (e.g., 0.05wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.5wt%, 0.7wt%, or 0.9wt%), based on the total weight of the aromatic oligomer and the aliphatic oligomer.

[0040] According to an embodiment of the present invention, the aromatic oligomer may be polyethylene terephthalate, poly(trimethylene terephthalate), poly(butylene terephthalate), poly(ethylene isophthalate), poly(trimethylene isophthalate), or poly(butylene isophthalate). The weight average molecular weight of the aromatic oligomer may be in the range of 800 g / mol to 3000 g / mol (e.g., 1000 g / mol, 1100 g / mol, 1500 g / mol, 2000 g / mol, 2100 g / mol, 2500 g / mol, or 2700 g / mol). According to an embodiment of the present invention, the aromatic oligomer is not polystyrene, or the aromatic oligomer is not an oligomer having repeating units derived from styrene. In other words, the first block of the present invention does not contain repeating units derived from styrene.

[0041] According to an embodiment of the present invention, the aliphatic oligomer may be polyoxyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, polyethylene propylene glycol, polyethanediol-co-adipate glycol, polybutanediol-co-adipate glycol, polyhexanediol-co-adipate glycol, polycaprolactone glycol, or poly(hexamethylene carbonate) glycol. The weight average molecular weight of the aliphatic oligomer may be in the range of 500 g / mol to 2000 g / mol (e.g., 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, 1500 g / mol, 1700 g / mol, or 2000 g / mol). In addition, the polyol is defined as above.

[0042] According to an embodiment of the present invention, the weight ratio of the aromatic oligomer to the aliphatic oligomer may be about 1:4 to 4:1, such as 1:3, 1:2, 1:1, 2:1, or 3:1. The amount of the polyol may be 0.01wt% to 2wt% (e.g., 0.2wt%, 0.3wt%, 0.5wt%, 0.7wt%, 1wt%, 1.2wt%, 1.5wt%, or 1.8wt%), based on the total weight of the aromatic oligomer and the aliphatic oligomer. According to an embodiment of the present invention, since the first block content of the block copolymer of the present invention is proportional to the amount of the aromatic oligomer, and the first block content of the block copolymer of the present invention is proportional to the amount of the aliphatic oligomer, the weight ratio of the aromatic oligomer and the aliphatic oligomer used to prepare the block copolymer may be equal to the ratio of the total weight of the first block to the total weight of the second block.

[0043] According to an embodiment of the present invention, recycled polyester materials can be used to prepare the block copolymer of the present invention. For example, the recycled polyester can be placed in a reactor, and a diol depolymerizing agent (such as ethylene glycol, propylene glycol, or butanediol) and a catalyst are added, and the temperature is raised to 140° C. to 180° C. under a nitrogen environment, and stirred to achieve an optimized chemical depolymerization reaction of the recycled polyester, and obtain an aromatic oligomer (used to form the first block), wherein the by-products removed in the depolymerization reaction can be collected by fractionation.

[0044] According to an embodiment of the present invention, the present invention also provides a method for preparing a foam, which is used for the foam of the present invention. The method for preparing the foam comprises: performing a foaming process on the composition to obtain the foam.

[0045] According to an embodiment of the present invention, the foaming process may be mechanical foaming, physical foaming, or chemical foaming. In combination with different foaming treatments, the foaming process may be carried out in the presence of a foaming agent. According to an embodiment of the present invention, the foaming agent may be an organic thermal decomposition type foaming agent, such as N, N'-dinitrosopentamethylenetetramine, azodicarbonamide, p, p'-oxybisbenzenesulfonylhydrazide, p-toluenesulfonylhydrazide, benzenesulfonylhydrazide, 3,3'-disulfonylhydrazide diphenyl sulfone, p-toluenesulfonylsemicarbazide, trihydrazinotriazine, or a combination thereof, but the present invention is not limited thereto. In addition, the foaming agent may be, for example, an inorganic thermal decomposition type foaming agent, such as sodium bicarbonate, potassium bicarbonate, ammonium bicarbonate, sodium carbonate, ammonium carbonate, or a combination thereof, but the present invention is not limited thereto. According to an embodiment of the present invention, when a foaming material is formed by a physical foaming process, a supercritical fluid may be used for foaming. The supercritical fluid may be carbon dioxide, water, methane, ethane, butane, propane, pentane, cyclopentane, hexane, ethylene, propylene, methanol, ethanol, acetone, methyl ethyl ketone, dichloromethane, nitrogen, or a combination thereof. The amount of the foaming agent added is not particularly limited, and those skilled in the art may adjust it according to actual needs.

[0046] In order to make the above contents and other purposes, features, and advantages of the present invention more clearly understood, preferred embodiments are given below and described in detail as follows.

[0047] Preparation of block copolymers

[0048] Preparation Example 1

[0049] 100 parts by weight of recycled polyester material (recycled PET bottle_polyethylene terephthalate), 50 parts by weight of ethylene glycol, and 0.02 parts by weight of antimony trioxide are added to a reaction bottle to obtain a first composition. Then, the first composition is stirred under a nitrogen environment, and the temperature of the reaction bottle is increased to 140°C to 160°C, so that the recycled polyester material and ethylene glycol undergo a depolymerization reaction. While reacting, by-products (i.e., excess ethylene glycol) are removed by fractionation, and the torque of the product in the reaction bottle is confirmed by a torque meter. When the measured torque value is greatly reduced (for example, from 80Nm to 30Nm), a mixture with polyethylene terephthalate is obtained as the reaction end point. Then, the polyethylene terephthalate in the mixture is analyzed by gel permeation chromatography (GPC), and it is known that the weight average molecular weight of the obtained polyethylene terephthalate is about 3000g / mol. According to an embodiment of the present invention, the obtained mixture containing polyethylene terephthalate can be further purified to obtain polyethylene terephthalate, or directly used for subsequent reactions. Here, the preparation of the block copolymer is carried out by taking direct use as an example.

[0050] Next, a mixture of polyethylene terephthalate, polytetramethylene ether glycol (weight average molecular weight of about 2000 g / mol), polyether tetraol (CAS number 115-77-5, purchased from ARCOS), and tetrabutyl titanate (TBT) are mixed to obtain a second composition. Here, the weight ratio of polyethylene terephthalate to polytetramethylene ether glycol is 7:3, the amount of polyether tetraol is 0.3wt%, based on the total weight of polyethylene terephthalate and polytetramethylene ether glycol; and the amount of tetrabutyl titanate is 0.025wt%, based on the total weight of polyethylene terephthalate and polytetramethylene ether glycol. The second composition is melt copolymerized at 210°C to 240°C and under vacuum, and the torque of the product in the reaction bottle is confirmed using a torque meter. When the measured torque value reaches 180 Nm, the reaction endpoint is taken, the vacuum is broken with nitrogen, the obtained product is placed in water, and pelletized after cooling, and dried to obtain a block copolymer (1) (having a branched structure). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (1) are measured, and the results are shown in Table 1. The weight average molecular weight (Mw) is measured by gel permeation chromatography (GPC); the hardness (i.e., Shore A hardness) is measured according to the method specified in ASTM D 2240; the tensile strength is measured according to the method specified in ASTM D3574; and the elongation is measured by a universal tensile machine according to the method specified in ASTM D412.

[0051] Next, the block copolymer (1) was heated to a temperature of 30°C above the melting point of the block copolymer (1), and the melt strength and melt viscosity of the block copolymer (1) were measured. The results are shown in Table 1. The melt strength can be measured using a rheometer (AR-G2, manufactured by TA Instruments, USA) in combination with a melt strength tester (Rheotens), the test temperature being 30°C above the melting point of the block copolymer and the roller pulling acceleration being 24 mm / s; and the melt viscosity can be measured using a rheometer at a shear rate of 100 sec. -1 The test temperature is the melting point of the block copolymer + 30°C, the plate length is 25 mm, and the gap is 200 μm.

[0052] Preparation Example 2

[0053] Preparation Example 2 was carried out according to the preparation method of the block copolymer (1) of Preparation Example 1, except that ethylene glycol was replaced by butanediol to obtain block copolymer (2). Then, the weight average molecular weight, hardness, tensile strength, and elongation of block copolymer (2) were measured, and the results are shown in Table 1.

[0054] Next, the block copolymer (2) was heated to a temperature of the melting point of the block copolymer (2) + 30° C., and the melt strength and melt viscosity of the block copolymer (2) were measured. The results are shown in Table 1.

[0055] Preparation Example 3

[0056] Preparation Example 3 was carried out according to the preparation method of the block copolymer (1) of Preparation Example 1, except that the polyester material (recycled PET bottle_polyethylene terephthalate) was replaced by a polyester material (recycled polyester textile_polyethylene isophthalate) to obtain a block copolymer (3). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (3) were measured, and the results are shown in Table 1.

[0057] Next, the block copolymer (3) was heated to a temperature of the melting point of the block copolymer (3) + 30° C., and the melt strength and melt viscosity of the block copolymer (3) were measured. The results are shown in Table 1.

[0058] Preparation Example 4

[0059] Preparation Example 4 was prepared according to the preparation method of the block copolymer (1) of Preparation Example 1, except that the polyester material (recycled PET bottle_polyethylene terephthalate) was replaced by a polyester material (recycled polyester textile_polyethylene isophthalate), and ethylene glycol was replaced by butanediol to obtain a block copolymer (4). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (4) were measured, and the results are shown in Table 1.

[0060] Next, the block copolymer (4) was heated to a temperature of the melting point of the block copolymer (4) + 30° C., and the melt strength and melt viscosity of the block copolymer (4) were measured. The results are shown in Table 1.

[0061] Preparation Example 5

[0062] Preparation Example 5 was prepared according to the preparation method of the block copolymer (1) of Preparation Example 3, except that the amount of the polyether tetraol was increased from 0.3wt% to 0.6wt%, thereby obtaining a block copolymer (5). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (5) were measured, and the results are shown in Table 1.

[0063] Next, the block copolymer (5) was heated to a temperature of the melting point of the block copolymer (5) + 30° C., and the melt strength and melt viscosity of the block copolymer (5) were measured. The results are shown in Table 1.

[0064] Preparation Example 6

[0065] Dimethyl terephthalate, butanediol, and antimony trioxide are added to a reaction bottle to obtain a first composition. The molar ratio of dimethyl terephthalate to butanediol is 1:1, and the amount of antimony trioxide is 0.02wt%, based on the total weight of dimethyl terephthalate and butanediol. Then, the first composition is stirred under a nitrogen environment, and the temperature of the reaction bottle is increased to 140°C to 160°C to allow dimethyl terephthalate and butanediol to react. After 90 minutes of reaction, polybutylene terephthalate is obtained. Then, the obtained polybutylene terephthalate is analyzed by gel permeation chromatography (GPC), and it is found that the weight average molecular weight of the obtained polybutylene terephthalate is about 3000g / mol.

[0066] Next, polybutylene terephthalate, polytetramethylene ether glycol (weight average molecular weight of 2000 g / mol), polyether tetraol (CAS number 115-77-5, purchased from ARCOS), and tetrabutyl titanate (TBT) are mixed to obtain a second composition. Here, the weight ratio of polybutylene terephthalate to polytetramethylene ether glycol is 7:3; and the amount of tetrabutyl titanate is 0.025wt%, based on the total weight of polybutylene terephthalate and polytetramethylene ether glycol. The second composition is subjected to melt copolymerization at 210°C to 240°C and vacuum, and the torque of the product in the reaction bottle is confirmed by a torque meter. When the measured torque value reaches 180Nm, it is regarded as the reaction end point. After breaking the vacuum with nitrogen, the obtained product is placed in water and pelletized after cooling, and dried to obtain a block copolymer (6). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (6) were measured, and the results are shown in Table 1. Next, the block copolymer (6) was heated to a temperature of its melting point + 30° C., and the melt strength and melt viscosity of the block copolymer (6) were measured, and the results are shown in Table 1.

[0067] Preparation Example 7

[0068] Dimethyl terephthalate, butanediol, and antimony trioxide are added to a reaction bottle to obtain a first composition. The molar ratio of dimethyl terephthalate to butanediol is 1:1, and the amount of antimony trioxide is 0.02wt%, based on the total weight of dimethyl terephthalate and butanediol. Then, the first composition is stirred under a nitrogen environment, and the temperature of the reaction bottle is increased to 140°C to 160°C to allow dimethyl terephthalate and butanediol to react. After 90 minutes of reaction, polybutylene terephthalate is obtained. Then, the obtained polybutylene terephthalate is analyzed by gel permeation chromatography (GPC), and it is found that the weight average molecular weight of the obtained polybutylene terephthalate is about 3000g / mol.

[0069] Next, polybutylene terephthalate, polytetramethylene ether glycol (weight average molecular weight of 2000 g / mol), and tetrabutyl titanate (TBT) are mixed to obtain a second composition. Here, the weight ratio of polybutylene terephthalate to polytetramethylene ether glycol is 7:3; and the amount of tetrabutyl titanate is 0.025wt%, based on the total weight of polybutylene terephthalate and polytetramethylene ether glycol. The second composition is subjected to melt copolymerization at 210°C to 240°C and under vacuum, and the torque of the product in the reaction bottle is confirmed by a torque meter. When the measured torque value reaches 180Nm, it is regarded as the reaction end point. After breaking the vacuum with nitrogen, the obtained product is placed in water and pelletized after cooling, and dried to obtain a block copolymer (7). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (7) are measured, and the results are shown in Table 1. Next, the block copolymer (7) was heated to a temperature of its melting point + 30° C., and the melt strength and melt viscosity of the block copolymer (7) were measured. The results are shown in Table 1.

[0070] Preparation Example 8

[0071] Dimethyl isophthalate, butanediol, and antimony trioxide are added to a reaction bottle to obtain a first composition. The molar ratio of dimethyl isophthalate to butanediol is 1:1, and the amount of antimony trioxide is 0.02wt%, based on the total weight of dimethyl isophthalate and butanediol. Then, the first composition is stirred under a nitrogen environment, and the temperature of the reaction bottle is increased to 140°C to 160°C to allow dimethyl isophthalate to react with butanediol. After 90 minutes of reaction, polybutylene terephthalate is obtained. Then, the obtained polybutylene isophthalate is analyzed by gel permeation chromatography (GPC), and it is found that the weight average molecular weight of the obtained polybutylene isophthalate is about 3000g / mol.

[0072] Next, polybutylene isophthalate, polytetramethylene ether glycol (weight average molecular weight of about 2000 g / mol), and tetrabutyl titanate (TBT) are mixed to obtain a second composition. Here, the weight ratio of polybutylene isophthalate to polytetramethylene ether glycol is 7:3; and the amount of tetrabutyl titanate is 0.025wt%, based on the total weight of polybutylene terephthalate and polytetramethylene ether glycol. The second composition is subjected to melt copolymerization at 210°C to 240°C and under vacuum, and the torque of the product in the reaction bottle is confirmed by a torque meter. When the measured torque value reaches 180Nm, it is regarded as the reaction end point. After breaking the vacuum with nitrogen, the obtained product is placed in water and pelletized after cooling, and dried to obtain a block copolymer (8). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (8) are measured, and the results are shown in Table 1. Next, the block copolymer (8) was heated to a temperature of its melting point + 30° C., and the melt strength and melt viscosity of the block copolymer (8) were measured. The results are shown in Table 1.

[0073] Table 1

[0074] Preparation Example 9

[0075] Preparation Example 9 was prepared according to the preparation method of the block copolymer (1) of Preparation Example 1, except that the weight ratio of polyethylene terephthalate to polytetramethylene ether glycol was adjusted from 7:3 to 1:5 to obtain a block copolymer (9). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (9) were measured, and the results are shown in Table 2. Next, the block copolymer (9) was heated to a temperature of the melting point of the block copolymer (9) + 30°C, and the melt strength and melt viscosity of the block copolymer (9) were measured, and the results are shown in Table 2.

[0076] Preparation Example 10

[0077] Preparation Example 10 was prepared according to the preparation method of the block copolymer (1) of Preparation Example 1, except that the weight ratio of polyethylene terephthalate to polytetramethylene ether glycol was adjusted from 7:3 to 5:1, to obtain a block copolymer (10). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (10) were measured, and the results are shown in Table 2. Next, the block copolymer (10) was heated to a temperature of the melting point of the block copolymer (10) + 30°C, and the melt strength and melt viscosity of the block copolymer (10) were measured, and the results are shown in Table 2.

[0078] Preparation Example 11

[0079] Polyethylene terephthalate is provided having a weight average molecular weight of about 450 g / mol.

[0080] Next, polyethylene terephthalate, polytetramethylene ether glycol (weight average molecular weight of 2000 g / mol), polyether tetraol (CAS number 115-77-5, purchased from ARCOS), and tetrabutyl titanate (TBT) are mixed to obtain a second composition. Here, the weight ratio of polyethylene terephthalate to polytetramethylene ether glycol is 1:4; the amount of polyether tetraol is 0.3wt%, based on the total weight of polyethylene terephthalate and polytetramethylene ether glycol; and the amount of tetrabutyl titanate is 0.025wt%, based on the total weight of polyethylene terephthalate and polytetramethylene ether glycol. The second composition is melt copolymerized at 210°C to 240°C and under vacuum, and the torque of the product in the reaction bottle is confirmed using a torque meter. When the measured torque value reaches 180 Nm, the reaction endpoint is taken, and the vacuum is broken with nitrogen, and the obtained product is placed in water and pelletized after cooling, and dried to obtain a block copolymer (11). Then, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (11) are measured, and the results are shown in Table 2. Then, the block copolymer (11) is heated to a temperature of its melting point + 30°C, and the melt strength and melt viscosity of the block copolymer (11) are measured, and the results are shown in Table 2.

[0081] Preparation Example 12

[0082] Polyethylene terephthalate is provided having a weight average molecular weight of about 4000 g / mol.

[0083] Next, polyethylene terephthalate, polytetramethylene ether glycol (weight average molecular weight of 2000 g / mol), polyether tetraol (CAS number 115-77-5, purchased from ARCOS), and tetrabutyl titanate (TBT) are mixed to obtain a second composition. Here, the weight ratio of polyethylene terephthalate to polytetramethylene ether glycol is 1:4; the amount of polyether tetraol is 0.3wt%, based on the total weight of polyethylene terephthalate and polytetramethylene ether glycol; and the amount of tetrabutyl titanate is 0.025wt%, based on the total weight of polyethylene terephthalate and polytetramethylene ether glycol. The second composition is melt copolymerized at 210°C to 240°C and under vacuum, and the torque of the product in the reaction bottle is confirmed using a torque meter. When the measured torque value reaches 180 Nm, the reaction endpoint is taken, and the vacuum is broken with nitrogen, and the obtained product is placed in water and pelletized after cooling, and dried to obtain a block copolymer (12). Then, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (12) are measured, and the results are shown in Table 2. Then, the block copolymer (12) is heated to a temperature of its melting point + 30°C, and the melt strength and melt viscosity of the block copolymer (12) are measured, and the results are shown in Table 2.

[0084] Preparation Example 13

[0085] Preparation Example 13 was prepared according to the preparation method of the block copolymer (1) of Preparation Example 1, except that the weight ratio of polyethylene terephthalate to polytetramethylene ether glycol was adjusted from 7:3 to 1:1, thereby obtaining a block copolymer (13). Next, the weight average molecular weight, hardness, tensile strength, and elongation of the block copolymer (13) were measured, and the results are shown in Table 2. Next, the block copolymer (13) was heated to a temperature of the melting point of the block copolymer (13) + 30°C, and the melt strength and melt viscosity of the block copolymer (13) were measured, and the results are shown in Table 2.

[0086] Table 2

[0087] Preparation of foam

[0088] Example 1

[0089] 100 parts by weight of the block copolymer (1) obtained in Preparation Example 1, 0.50 parts by weight of a flow aid (product number Zn-St, purchased from ACROS), and 0.2 parts by weight of an antioxidant (product number AO1010, purchased from ACROS) were mixed. After uniform mixing, the resulting mixture was added to a twin-screw compounding extruder (25ψ, L / D=42) for compounding and compounding. The process conditions were a screw temperature of 200°C to 230°C and a rotation speed of 150rpm to 300rpm. After compounding for 3 minutes, the resulting mixture was placed in a supercritical foaming injection molding machine (J450EL-MuCell, produced by Japan Steel Works LTD.), and foamed under the conditions of a temperature of 190°C to 210°C, a gas pressure of 2000psi, and a nitrogen to carbon dioxide ratio of 7:3 to obtain a foam (1). Next, the density and resilience of the foam (1) were measured. The results are shown in Table 3. The density and resilience of the foam can be measured according to the method specified in standard ASTM D3574.

[0090] Embodiment 2-6

[0091] Examples 2-6 were prepared according to the method for preparing the foam (1) of Example 1, except that block copolymers (2)-(5) and (13) were used to replace block copolymer (1) to obtain foams (2)-(6). Next, the density and resilience of the foams (2)-(6) were measured, and the results are shown in Table 3.

[0092] Comparative Examples 1-6

[0093] Comparative Examples 1-6 were prepared according to the method for preparing the foam (1) of Example 1, except that block copolymers (7)-(12) were used to replace block copolymer (1) to obtain foams (7)-(11) (wherein block copolymer (12) could not be foamed). Next, the density and resilience of the foams (7)-(11) were measured. The results are shown in Table 3.

[0094] Table 3

[0095] As shown in Table 1 and Table 3, since polyether tetraol was not added when preparing the block copolymers in Preparation Examples 7 and 8, the obtained block copolymers do not have a branched structure, and their melt strength is lower than 2mN, and their viscosity is higher than 1500Pa. Therefore, the foams obtained in Comparative Examples 1 and 2 have a higher density (ie, a poorer expansion ratio) and a lower resilience.

[0096] It can be seen from Table 2 and Table 3 that, since the weight ratio of the first block to the second block in the preparation of the block copolymers in Preparation Examples 9 and 10 did not fall within the range of 1:4 to 4:1, the melt strength of the obtained block copolymers was lower than 3 mN. Therefore, the foams obtained in Comparative Examples 3 and 4 had a higher density (i.e., a poorer expansion ratio) and a lower resilience.

[0097] As shown in Table 2 and Table 3, the molecular weight of polyethylene terephthalate (first block) in the preparation of block copolymers in Preparation Examples 11 and 12 is too low or too high, and the melt strength of the obtained block copolymers is less than 10 mN. The foam obtained in Comparative Example 5 has a higher density (i.e., a poorer foaming ratio) and a lower resilience. In addition, Comparative Example 6 uses the block copolymer of Preparation Example 12 to prepare a foam, but no foam can be obtained.

[0098] According to an embodiment of the present invention, the block copolymer of the present invention comprises a first block, a second block, and a linking group. Since the linking group is a residue of dehydrogenation of a polyol, the block copolymer has a branched structure, which increases the degree of entanglement of the molecular chains of the block copolymer, further optimizes the melt strength of the block copolymer, and improves crystallinity and fluidity. In this way, the foam of the present invention can have low density, high flexibility, high resilience, and high physical property maintenance rate (such as tensile strength maintenance rate, flexural strength maintenance rate, tear strength maintenance rate, and compression permanent deformation maintenance rate), which is suitable for application in the fields of high-end sports goods or shoe materials.

[0099] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A foamed body, comprising a foaming material and a plurality of cells, wherein the plurality of cells are disposed in the foaming material, wherein the foaming material is prepared from a composition, the composition comprising: 0.01-2.0 parts by weight of a flow aid; and 100 parts by weight of a block copolymer, wherein the block copolymer comprises a first block, a second block, and a connecting group; the first block is connected to the second block via the connecting group; the first block is an aromatic polyester block; the second block is an aliphatic polyether block, an aliphatic polyester block, or an aliphatic polycarbonate block; and the connecting group is a residue of dehydrogenation of a polyol, wherein the polyol is a triol, a tetraol, a pentaol, a hexaol, a heptaol, or an octaol. 2 . The foam according to claim 1 , wherein in the block copolymer, a ratio of the total weight of the first block to the total weight of the second block is 1:4 to 4:

1. 3 . The foam according to claim 1 , wherein the density of the foam is 0.05 to 0.2 g / mL, and the resilience of the foam is 60% to 80%. 4 . The foam according to claim 1 , wherein the melt strength of the block copolymer is 10 mN to 20 mN at a temperature of the melting point of the block copolymer + 30° C.

5. The foam according to claim 1, wherein the temperature is at the melting point of the block copolymer + 30°C and the shear rate is 100 sec -1 Under the condition of s. The foam according to claim 1 , wherein the hardness of the block copolymer is 30D-70D. The foam according to claim 1 , wherein the particle size distribution D90 of the cells is 10 μm to 400 μm.

8. The foam of claim 1, wherein the first block is a recycled aromatic polyester block.

9. The foam according to claim 1, wherein the first block is a polyethylene terephthalate block, a polypropylene terephthalate block, a polybutylene terephthalate block, a polyethylene isophthalate block, a polypropylene isophthalate block, or a polybutylene isophthalate block. 10 . The foam according to claim 1 , wherein the weight average molecular weight of the first block is 800 g / mol to 3000 g / mol.

11. The foam according to claim 1, wherein the second block is a polyethylene glycol block, a polypropylene glycol block, a polytetramethylene ether glycol block, a polyethylene propylene glycol block, a poly(ethylene glycol-adipate) glycol block, a poly(butylene glycol-adipate) glycol block, a poly(hexanediol-adipate) glycol block, a polycaprolactone glycol block, or a poly(hexamethylene carbonate) glycol block. 12 . The foam according to claim 1 , wherein the weight average molecular weight of the second block is 500 g / mol to 2000 g / mol.

13. The foam according to claim 1, wherein the polyol is an aliphatic polyether triol, an aromatic polyether triol, an aliphatic polyester triol, an aromatic polyester triol, an aliphatic polyether tetraol, an aromatic polyether tetraol, an aliphatic polyester tetraol, an aliphatic polyether pentaol, an aromatic polyether pentaol, an aliphatic polyester pentaol, an aromatic polyester pentaol, an aliphatic polyether hexaol, an aromatic polyether hexaol, an aliphatic polyester hexaol, an aromatic polyester hexaol, an aliphatic polyether heptaol, an aromatic polyether heptaol, an aliphatic polyester heptaol, an aromatic polyester heptaol, an aliphatic polyether octaol, an aromatic polyether octaol, an aliphatic polyester octaol, or an aromatic polyester octaol having a weight average molecular weight of 800 g / mol to 3000 g / mol. 14 . The foam according to claim 1 , wherein the content of the linking group is 0.1 wt % to 2 wt %, based on the total weight of the first block and the second block. 15 . The foam according to claim 1 , wherein the block copolymer has a weight average molecular weight of 20,000 g / mol to 100,000 g / mol.

16. The foam according to claim 1, wherein the flow aid is stearic acid, stearate, stearamide, paraffin, oleamide, tristearin, monostearin, or a combination thereof.